Western Materialism and Modernism's Philosophical Sources - Suraiya IT (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2023)
One of materialism's and modernism's most serious flaws is their failure to take a holistic picture of human life. Transcendental ideals are rejected by almost all modernist ideologists. To put it another way, there is no objective, absolute standard for truth. Truth and moral standards, on the other hand, are only relative, with validity restricted to time, location, and situation. Modernists label societies founded on divine revelation as